Re-examining the membership and origin of the ϵ Cha association - Murphy, Simon J.; Lawson, Warrick; Bessell, Michael S. (Monthly notices of the Royal Astronomical Society, 2013)
We present a comprehensive investigation of the ϵ Chamaeleontis association (ϵ Cha), one of several young moving groups spread across the southern sky. We re-assess the putative membership of ϵ Cha using the best available proper motion and spectroscopic measurements, including new ANU 2.3-m/Wide Field Spectrograph observations. After applying a kinematic analysis, our final membership comprises 35-41 stars from B9 to mid-M spectral types, with a mean distance of 110 ± 7 pc and a mean space motion of (U, V, W) = (−10.9 ± 0.8, −20.4 ± 1.3, −9.9 ± 1.4) km s−1. Theoretical evolutionary models suggest ϵ Cha is 3-5 Myr old, distinguishing it as the youngest moving group in the solar neighbourhood. 15 members show 3-22 μm spectral energy distributions attributable to circumstellar discs, including 11 stars which appear to be actively accreting. ϵ Cha's disc and accretion fractions ($29^{+8}_{-6}$ and $32^{+9}_{-7}$ per cent, respectively) are both consistent with a typical 3-5 Myr old population. Multi-epoch spectroscopy reveals three M-type members with broad and highly variable Hα emission as well as several new spectroscopic binaries. We reject 11 stars proposed as members in the literature and suggest they may belong to the background Cha I and II clouds or other nearby young groups. Our analysis underscores the importance of a holistic and conservative approach to assigning young stars to kinematic groups, many of which have only subtly different properties and ill-defined memberships. We conclude with a brief discussion of ϵ Cha's connection to the young open cluster η Cha and the Scorpius-Centaurus OB association (Sco-Cen). Contrary to earlier studies which assumed η and ϵ Cha are coeval and were born in the same location, we find the groups were separated by ∼30 pc when η Cha formed 4-8 Myr ago in the outskirts of Sco-Cen, 1-3 Myr before the majority of ϵ Cha members.